Crystallization and preliminary X-ray diffraction analysis of various enzyme-substrate complexes of isopropylmalate dehydrogenase from thermus thermophilus - Merli, Angelo; Manikandan, Karuppasamy; Graczer, Eva; Schuldt, Linda; Singh, Rajesh Kumar; Zavodszky, Peter; Vas, Maria; Weiss, Manfred S. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2010)
The Thermus thermophilus 3-isopropylmalate dehydrogenase (Tt-IPMDH) enzyme catalyses the penultimate step of the leucine-biosynthesis pathway. It converts (2R,3S)-3-isopropylmalate to (2S)-2-isopropyl-3-oxosuccinate in the presence of divalent Mg(2+) or Mn(2+) and with the help of NAD(+). In order to elucidate the detailed structural and functional mode of the enzymatic reaction, crystals of Tt-IPMDH were grown in the presence of various combinations of substrate and/or cofactors. Here, the crystallization, data collection and preliminary crystallographic analyses of six such complexes are reported.